Efek Longitudinal Vortex Dihasilkan dari Vortex Generator Jenis Concave Delta dan Rectangular Winglet terhadap Perbaikan Perpindahan Panas: Visualisasi Aliran/Studi Eksperimental - Syaiful, Syaiful (Jurnal Rekayasa Mesin, 2017)
The generation of longitudinal vortex to enhance the rate of heat transfer is a passive method that has been widely considered recently. This consideration is based on improving the energy efficiency and optimum design of a heat exchanger. Therefore, this study is focused on the experimental test and flow visualization of effects of longitudinal vortex generated from concave delta and rectangular winglet vortex generators on the increase of heat transfer rate. This is performed by draining the air inside the channel with variations in velocities ranging from 0.4 m/s - 2 m/s through a rectangular plate mounted with the vortex generators. The attack angle of the flow against the vortex generator is 15Â°. The flow visualization is performed by firing a laser beam on a cylindrical glass rod at certain locations to capture the longitudinal vortex formed on the cross-section plane. Inlet and outlet air temperatures and wall temperature are measured using the thermocouples. The results show that the longitudinal vortices are formed in the wake region of the vortex generators. By using the concave delta winglet, the heat transfer rate can be increased up to 51% and increased to 85% using the concave rectangular winglet.